SOCIAL ANXIETY DISORDER RATIO AND SOME RELATED FACTORS IN THE STUDENT OF NGUYEN KHUYEN HIGH SCHOOL, BINH PHUOC (Vietnam Journal of Community Medicine, 2021)
Social anxiety disorder is a common adolescent anxiety disorder with rates ranging from 9.1% to 44%between countries around the world. In Vietnam, research on this disorder is quite limited. Socialphobia affects many aspects of life, such as school, work, and increases the risk of depression andsuicide in adults. However, finding treatment, the recovery rate is still quite low. So early screeningfor this disorder is necessary. The study conducted on 430 students participating in the study, theprevalence of phobias on the LSAS scale was 42.3%. 35.7% and 37.4% respectively. Multivariateanalysis showed a statistically significant relationship between social phobia and factors such aslack of confidence in appearance, mother’s occupation (p
Keywords: Social anxiety disorder, student, high school